Prenatal identification of novel HSPG2 variants associated with dyssegmental dysplasia Silverman-Handmaker type - Yunxia Wang; Hui Wang (IMR Press, 2022)
Background: We aimed to analyze mutations of the pathogenic gene in dyssegmental dysplasia Silverman-Handmaker (DDSH) type associated with the Heparin sulfate proteoglycan 2 (HSPG2) gene. Case: Prenatal testing for genetic mutations associated with fetal DDSH were performed on a pregnant woman with previous history of carrying a fetus with short limb malformation at the 17th week of gestation. DNA was extracted from amniotic fluid and next-generation sequencing-based deep panel sequencing was performed on the Illumina NextSeq platform to identify possible causative mutations of DDSH. Results: Two novel heterozygous mutations in HSPG2 gene, c.6001dupC (p. R2001pfs*19) and c.11207G>A (p. R373Q), were identified and associated with the DDSH diagnosis. Conclusion: This is the first report to prenatally identify novel mutations in HSPG2 that confirms a DDSH diagnosis.